Prediction of In-plane Stiffness for the Cold-formed Steel Frame of the Wall Panel Structure - Benchaphong, Apai; Hongthong, Rattanasak; Konkong, Chitsirin; Konkong, Nirut (Periodica Polytechnica Civil Engineering, 2022)
The purpose of this research was to study the lateral deformation behavior of cold-formed steel wall panel structures using experimental tests, finite element analysis and analytical methods to study the lateral stiffness of these structures. The wall panel structures were tested by full-scale experiments the experimental results of which were verified by a 3D-finite element model. The verification results showed a good correlation between the experimental tests and a finite element model. The single-column spring model was proposed for an elastic lateral stiffness analysis of the cold-formed steel wall panel structures that were formed by combinations of a guide cantilever beam and springs connection. The spring constants were defined by using the stiffness of the stub-chord connection and the bending stiffness of the chord. The experiments tests and finite element analysis were used to verify this single-column spring model. The comparison results showed good agreement between the analytical prediction, finite element analysis and experimental data in the case of the primary type of cold-formed wall structure. The proposed procedure was an efficient method for elastic lateral deformation analysis of cold-formed wall panel structures which can be used for such configurations.